Maillard reaction-based conjugation of pea protein and prebiotic (polydextrose): optimization, characterization, and functional properties enhancement - Khan, Hina; Mudgil, Priti; Alkaabi, Shaikha Ali Salem; AlRashdi, Yamna Hamad Salem; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2024)
There is a growing demand for plant-based protein ingredients with improved functionality for use in diverse food and nutraceutical applications. In line with this, the current study aimed to investigate the effect of plant protein-prebiotic (polydextrose) conjugation on the technofunctional properties (emulsification, solubility, fat absorption and foaming) of pea proteins through wet heating Maillard reaction. Pea protein (PeP) was conjugated with polydextrose by incubating the mixture at various process conditions (protein: prebiotic mass ratios, temperature, and time). Response surface methodology coupled with Box-Behnken design was used to optimize multiple responses, including conjugation efficiency (CE), emulsifying activity (EAI), and foaming capacity (FC). The pea protein conjugate (optimized value) showed improved solubility throughout a wide pH (2-10) range and higher emulsification activity than pea protein alone. The development of conjugates (PeC) was validated through ultraviolet-visible spectroscopy and o-Phthaldialdehyde (OPA) assay. Browning index, FT-IR spectra, thermal properties, and SEM micrographs were analyzed for the conjugate (PeC) obtained at optimized values. The FTIR spectra of the conjugates showed new peaks at 3100-3480 cm -1 and 1000 -1166 cm -1 indicating conjugation. The Maillard conjugation increased the proportion of β-turn, random coil, accompanied by a decrease in α-helix, β-sheet. These conformational changes were associated to the improved techno-functional properties of the pea protein, offering potential applications in the formulation of plant-based foods and beverages.